Irinotecan-Induced Steatohepatitis: Current Insights - Han, Jun; Zhang, Jing; Zhang, Chengliang (Frontiers in Oncology, 2021)
The hepatotoxicity of irinotecan is drawing wide concern nowadays due to the widespread use of this chemotherapeutic against various solid tumors, particularly metastatic colorectal cancer. Irinotecan-induced hepatotoxicity mainly manifests as transaminase increase and steatosis with or without transaminase increase, and is accompanied by vacuolization, and lobular inflammation. Irinotecan-induced steatohepatitis (IIS) increases the risk of morbidity and mortality in patients with colorectal cancer liver metastasis (CRCLM). The major risks and predisposing factors for IIS include high body mass index (BMI) or obesity, diabetes, and high-fat diet. Mitochondrial dysfunction and autophagy impairment may be involved in the pathogenesis of IIS. However, there is currently no effective preventive or therapeutic treatment for this condition. Thus, the precise mechanisms underlying the pathogenesis of IIS should be deciphered for the development of therapeutic drugs. This review summarizes the current knowledge and research progress on IIS.